The effect of a supra-cognitive strategy on achievement and creative thinking in social studies for eleventh grade students in the Sultanate of Oman - Alwahshi, Aisha Omair Mohammed; Abdulrahman, Asmaa (Journal of Educational and Psychological Sciences, 2020)
The study aimed to investigate the impact of the above- cognitive teaching strategy on achievement and creative thinking among students of the eleventh grade in the Sultanate of Oman, and the study used the semi- experimental approach. It was implemented in 55 grade 11 students from Um Attiya School (5- 12). They were divided into two groups: an experimental (27) female student who studied using the post- cognitive teaching strategy and the other control (28) studied by the traditional method. The study experiment was continued for 4 weeks. The results of the study showed that the experimental group obtained a total average of (18.58 out of 20) in academic achievement and (54.34 of 80) in creative thinking; In return for the control’s average score of (13.43 out of 20) in academic achievement and (12.86 out of 80) in creative thinking; There were statistically significant differences between the arithmetic averages for the performance of students of the experimental and control groups at the level of significance (0,05) in favor of the experimental group, and the presence of a statistical function in the arithmetic mean of the experimental group in the pre and post exam (achievement, and creative thinking scale) in favor of the post- attributable to the teaching strategy Super cognitive. In the light of the results, the researcher recommended the necessity of including curricula for metacognitive skills and holding training courses for supervisors and teachers in the field of teaching social studies to learn about the above- knowledge teaching strategy in view of its effectiveness in teaching, as the researcher suggested a set of researches in this field.